The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2147/ott.s243212
|View full text |Cite
|
Sign up to set email alerts
|

<p>Sinomenine Inhibits Non-Small Cell Lung Cancer via Downregulation of Hexokinases II-Mediated Aerobic Glycolysis</p>

Abstract: These authors contributed equally to this workBackground: Addiction to aerobic glycolysis is a common metabolic phenotype in human non-small cell lung cancer (NSCLC). The natural product Sinomenine (Sin) exhibits significant anti-tumor effects in various human cancers. However, the underlying mechanism remains elusive. Methods: The inhibitory effect of Sin on NSCLC cells was determined by MTS and soft agar assays. The glycolysis efficacy of NSCLC cells was examined by glucose uptake and lactate production. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Accumulating evidence has demonstrated that aerobic glycolysis is a key hallmark of cancer cells (9,10); molecules involved in the aerobic glycolysis pathway may be potential targets in cancer therapy, including cervical cancer (7,11). Therefore, certain metabolic enzymes such as Hexokinase 2, Phosphoinositide-Dependent Kinase 1 and Lactate dehydrogenase A chain (LDHA) involved in aerobic glycolysis have been identified as potential therapeutic targets (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that aerobic glycolysis is a key hallmark of cancer cells (9,10); molecules involved in the aerobic glycolysis pathway may be potential targets in cancer therapy, including cervical cancer (7,11). Therefore, certain metabolic enzymes such as Hexokinase 2, Phosphoinositide-Dependent Kinase 1 and Lactate dehydrogenase A chain (LDHA) involved in aerobic glycolysis have been identified as potential therapeutic targets (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…1 ): Glycolysis, which takes place under anaerobic conditions, and complete oxidation, which occurs under aerobic conditions ( 10 ). In the 1920s, Otto Heinrich Warburg discovered that cancer cells, unlike normal cells, use the glycolytic pathway to obtain energy for growth even in the presence of oxygen, which is a phenomenon known as ‘aerobic glycolysis’ or the Warburg effect ( 9 ), and aerobic glycolysis is a common metabolic phenotype in NSCLC ( 11 ). In positron emission tomography (PET)/CT, the high rate of glycolysis in NSCLC is reflected by the high uptake of 18F-fluorodeoxyglucose at the corresponding tumor sites ( 12 ).…”
Section: Aerobic Glycolytic Pathways and Targeted Therapy In Nsclcmentioning
confidence: 99%
“…The unfavorable prognosis (lower OS and DFS) was correlated with higher PKM2 expression, e.g., in breast, hepatocellular cancer, as well as in tongue and esophagus squamous cell carcinoma [ 189 192 ]. In correlation with glucose utilization, elevated HK2 was recently described in patients’ biopsies of esophageal, renal, lung, cervical, colon, and breast cancers [ 193 195 ]. The analyses of LDHA and PDK1 in situ protein expression also showed association with poor survival and therapy resistance in many malignancies (colon, breast, uterine, pancreas, lung, renal, gastric cancers, CNS malignancies, etc.).…”
Section: In Situ Metabolic Protein Expression Alterations An...mentioning
confidence: 99%